The effect of light-emitting diode-mediated photobiomodulation therapy on orthodontic tooth movement: A literature review - Rashin Bahrami; Nariman Nikparto; Fateme Gharibpour; Maryam Pourhajibagher; Abbas Bahador (Photodiagnosis and Photodynamic Therapy)
This study aims to review and analyze the impact of light-emitting diode (LED) photobiomodulation (PBM) therapy on orthodontic tooth movement. This non-invasive technique is proposed to reduce time-related side effects, such as white spot lesions, dental caries, and root resorption. Five studies were included in the review, comprising two animal studies (ages 10 and 12 weeks) and three human studies (ages ranging from 15 to 17 years). All studies applied PBM concurrently with force application using sliding mechanics for canine retraction (three studies) and molar protraction (two studies). Two studies employed LEDs with a wavelength of 850 nm, with an exposure time of 5 min daily. Another two studies used LEDs with a wavelength of 618 nm, with an exposure time of 20 min daily. In summary, these studies demonstrated that LED-mediated PBM enhanced orthodontic tooth movement by 33 % (a 1.36-fold increase) compared to the control group. The mean tooth movement per month was 1.55 ± 0.33 mm, which was higher than the control group's average of 1.06 ± 0.35 mm. Also, no studies demonstrated any side effects such as anchorage loss, root resorption, canine rotation, or tooth inclinations. In conclusion, LED-mediated PBM (at wavelengths of 618 nm and 850 nm) can accelerate orthodontic tooth movement without adverse effects, thanks to its biostimulatory properties. Given the advantages of LEDs over traditional lasers—particularly their lower cost and easier application—this method shows promise as a tool to accelerate tooth movement, potentially reducing treatment time and associated side effects.